PERBEDAAN PENGARUH METODE LATIHAN PLYOMETRIK DAN BERBEBAN TERHADAP PENINGKATAN KECEPATAN SMASH BOLAVOLI DITINJAU DARI KEKUATAN OTOT LENGAN - Primayanti, Intan (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
The objective of research to find out(1) Plyometrik and weight training methode effect Â differences Â towardÂ theÂ increased Â speed Â ofÂ volleyball Â smash, Â (2)Â increased Â speed differences of volleyball smash between students with high and low arm muscle strength, (3) Effect of interaction between training method and arm muscle strength toward increased speed of volleyball smash.This study used the experimental method consists of three variables, namely manipulative independent variable (training methods), attributive variable (arm muscle strength), and the dependent variable (volleyball smash speed). The study design was 2x2 factorial design. The sample used in this study were male student from coaching Department of Nusantara PGRI Kediri University , amounting to 20 people with purposive random sampling. Arm muscle strength data obtained from test of arm muscle strength with hand dynamometer tools, while the smash speed data obtained from the smash speed test which are recorded with high-speed camera and then analyzed using Adobe Primiere 6.5 (AVI) computer program with Pinnacle hardware system pro-one instrument.Data analysis using ANAVA. Prior to testing with ANAVA, Â usingÂ normality test sample Â (Lillifors Â Test Â with Â Î± = 0. 05) and Â homogeneity of varianceÂ test (BartletÂ testÂ Â withÂ Î± =Â 0.05) first. Based on the results of data analysis show that: (1) There is an effect differences between the plyometrik and load exercise toward increased speed of volleyball smash (Fo = 5.185> Ft =4.49), (2) There is a difference in increasing the speed of volleyball smash between students who have the arm muscle strength high and low (Fo = 4.717> Ft = 4.49), (3) There is interaction between training method and arm muscle strength toward volleyball smash speed (Fo = 6.487> Ft = 4.49).